Do fracture zones define continental margin segmentation? Evidence from the French Guiana margin - Greenroyd, C; Peirce, C; Rodger, M; Watts, A; Hobbs, R (2008)
Plate reconstructions suggest that the French Guiana margin in the west equatorial Atlantic is a highly segmented margin with both rift- and transform-style features. We describe here the results of modelling coincident multi-channel and wide-angle seismic, gravity and magnetic data acquired along two transects of this margin. The resulting models not only highlight the degree of structural segmentation but also demonstrate the effect of trans-tension on margin evolution. As a whole, the margin is characterised by 35-37 km thick pre-rift continental crust which is separated from unusually thin oceanic crust (3-4 km) by thinned continental and/or transitional regions. To the north, the margin exhibits a 320 km wide zone of thinned continental crust adjacent to a narrow ocean-continent transition, and is interpreted as a transform margin where the wide zone of thinned crust is a result of profile orientation being highly oblique to the direction of rifting. Approximately 240 km to the south, the margin is characterised by a 70 km wide zone of thinned continental crust which is wider than typical for transform, and narrower than typical for rifted margins. This crustal structure is interpreted to reflect a "leaky" transform formed by trans-tensional extension. These observations suggest that fracture zone influenced geometry of equatorial Atlantic rifting, did not produce a well-defined margin crustal structure, but instead resulted in margin segments which display characteristics of both rift and transform tectonic processes. The associated abundance of fracture zones has likely also affected the post-rift evolution of the margin, and provided topographic basement highs which acted as sediment dams to the northwards flux of sediment from the Amazon. © 2008 Elsevier B.V. All rights reserved.